Assessment of Comp etition in Banking Sector of Namibia - Kandaswamy R, Vijayakumar; Ndaghangwep, Nelson; Gnitchogna, Rodrigue (IJRDO - Journal of Business Management, 2018)
Competition plays a regulatory function in balancing demand and supply, and commercial banks in developing countries take a pivotal role in creating economic growth. They finance trade, industry, agriculture and are the main contributor to capital formation. It is therefore important to measure the competitiveness of commercial banks in developing economies. This paper uses of a modern and more robust analysis technique the Profit Elasticity model, along with the more conventional PanzarRosse model, to examine the competitiveness of commercial banks in Namibia. The loan market data from 2002 to 2016 are utilized for this study. Equally, as the contribution of mortgages to bank assets in Namibia is high, the analysis are solelyconducted on the home loan market, one of the largest sector of the loan market inNamibia.